IDENTIFICATION OF EARLY CHILDHOOD EDUCATION (ECE) MANAGEMENT - Upik Elok Endang Rasmani (Early Childhood Education and Development Journal, 2020)
The purpose of this study is to determine problems related to Early Childhood Education (ECE) Management. It uses a qualitative descriptive approach with case studies. Samples were selected using purposive and snowball sampling techniques, while interviews, observation, and documentation were used in data collection. From the data analysis techniques with an independent sample t-test, an average pretest of the experimental group was 5.45 and post-test 9.60. The data analysis showed a significance value of 0.000 based on decision making with ?> 0.05. The samples for the study were administrative officers and the teachers in Warga Kindergarten and Aulia Kindergarten at Surakarta for the experimental and control group. The results of the analysis indicate that there are ECE management problems lessens the institutions’ quality. Also, the management identification was needed to improve ECE management. This is because the level of significance before directions was greater than 0.05 and smaller than 0.05 after the direction. Therefore, the values before and after the directives have significant differences.